2010
DOI: 10.1111/j.1365-2567.2010.03286.x
|View full text |Cite
|
Sign up to set email alerts
|

Proviral integration site 2 is required for interleukin‐6 expression induced by interleukin‐1, tumour necrosis factor‐α and lipopolysaccharide

Abstract: SummaryPIM (proviral integration site) kinases are a distinct class of serine/threonine-specific kinases consisting of PIM1, PIM2 and PIM3. PIM2 is known to function in apoptosis pathways. Expression of PIM2 is highly induced by pro-inflammatory stimuli but the role of PIM2 in the expression of pro-inflammatory cytokines is unclear. In this study, we showed that over-expression of PIM2 in HeLa cells as well as in human umbilical vein endothelial cells enhanced interleukin-1b (IL-1b) -induced and tumour necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…12 However, PIM2 has been shown to be required for interleukin 6 expression, which is regulated at least in part by STAT5. 14,15 These data suggest that PIM kinases may augment STAT5 activity through a feed-forward mechanism to maximally amplify the STAT5 proliferative signal. In the responder KG1 cell line, STAT5A/B is required for regulating CD25 mRNA expression, as knockdown of STAT5A/B significantly repressed the mRNA levels of CD25 ( Figure 3Fi) and resulted in a marked decrease of CD25 protein levels ( Figure 3Fii).…”
Section: Identification Of Aml Cell Lines Sensitive To the Inhibitionmentioning
confidence: 95%
See 1 more Smart Citation
“…12 However, PIM2 has been shown to be required for interleukin 6 expression, which is regulated at least in part by STAT5. 14,15 These data suggest that PIM kinases may augment STAT5 activity through a feed-forward mechanism to maximally amplify the STAT5 proliferative signal. In the responder KG1 cell line, STAT5A/B is required for regulating CD25 mRNA expression, as knockdown of STAT5A/B significantly repressed the mRNA levels of CD25 ( Figure 3Fi) and resulted in a marked decrease of CD25 protein levels ( Figure 3Fii).…”
Section: Identification Of Aml Cell Lines Sensitive To the Inhibitionmentioning
confidence: 95%
“…Nevertheless, the fact that STAT5 activation induces interleukin 6 gene transcription, and that PIM2 has been shown to be required for interleukin 6 expression, implies that a PIM family-mediated feed-forward mechanism regulating STAT activity may exist. 14,15 The PIM serine/threonine kinase family is composed of 3 highly homologous proteins: PIM1, PIM2, and PIM3. Functional redundancy of the 3 PIM kinases has previously been demonstrated both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…cDNA synthesis and TaqMan Real Time PCR were performed as described previously (25)(26)(27). TaqMan quantitative PCR was performed on a 7900HT Real Time PCR System (Applied Biosystems).…”
Section: Rna Extraction Quantitative Rt-pcrmentioning
confidence: 99%
“…PIM2 was first discovered in lymphomas in mice and found to have anti-apoptotic effects as well as several other functions including cell cycle regulation, cell proliferation, and transcriptional activity [2,[4][5][6][7][8]. Several studies have demonstrated that PIM2 plays an important role in cell survival and apoptosis in tumors [9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%